Trends in industrialization and commercialization of IgY technology - Yakhkeshi, Saeed; Wu, Rao; Chelliappan, Brindha; Zhang, Xiaoying (Frontiers in Immunology, 2022)
IgY technology refers to the strategic production process involved in generating avian immunoglobulin (IgY) against target antigens in a much more cost-effective manner with broad applications in the fields of diagnostics, prophylaxis, and therapeutics for both human and veterinary medicine. Over the past decade, promising progress in this research area has been evident from the steep increase in the number of registered manufacturing companies involved in the production of IgY products, the number of patents, and the notable number of clinical trials underway. Hence, it is crucial to conduct a prospective analysis of the commercialization and marketing potential of IgY-based commercial products for large-scale applications. This review revealed that the number of IgY patent applications increased steeply after 2010, with the highest of 77 patents filed in 2021. In addition, 73 industries are reportedly involved in marketing IgY products, out of which 27 were promoting biotherapeutics for human and veterinary medicine and 46 were in the diagnostic field. IgY antibodies are being used as primary and secondary antibodies, with approximately 3729 and 846 products, respectively. Biotherapeutic product consumption has notably increased as a food supplement and as a topical application in human and veterinary medicine, which are under different clinical phases of development to reach the market with around 80 and 56 products, respectively. In contrast, the number of IgY products as parenteral administrations and licensed drugs is not well developed given the lack of technical standards established for IgY registration and industrialization, as well as the restriction of the nature of polyclonal antibodies. However, recent ongoing research on functional IgY fragments indicates a promising area for IgY applications in the near future. Therefore, retrospective analysis with speculations is mandatory for IgY technology maturation toward industrialization and commercialization.